2023
DOI: 10.3390/cancers15184530
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of STAT4 Variants and Risk of Hepatocellular Carcinoma in Latin Americans and Europeans

Alan Ayoub,
Chimaobi M. Anugwom,
Jhon Prieto
et al.

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer death worldwide. The STAT4 rs7574865 genetic variant has been associated with an increased risk of developing HCC in Asian populations. However, this association has not been studied in Latin America and is poorly assessed in European populations. This case-control study investigated the association between STAT4 rs7574865 and HCC risk in these populations. We evaluated DNA samples from seven medical institutions across six Latin American coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Recently, our team found no significant association between STAT4, TLL1, or MBOAT7 risk alleles and HCC development in Latin America. [7][8][9] Notably, these studies also used self-reported ancestry and found that Europeans and Latin Americans of self-reported European descent had a similar distribution of some risk alleles, suggesting that self-reported ancestry may carry validity in ancestral research. 7,9 In summary, we propose the possibility of ancestry-driven NAFLD and NAFLD-HCC and further cement the importance of genetic diversity inclusion in the study of Latin American populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our team found no significant association between STAT4, TLL1, or MBOAT7 risk alleles and HCC development in Latin America. [7][8][9] Notably, these studies also used self-reported ancestry and found that Europeans and Latin Americans of self-reported European descent had a similar distribution of some risk alleles, suggesting that self-reported ancestry may carry validity in ancestral research. 7,9 In summary, we propose the possibility of ancestry-driven NAFLD and NAFLD-HCC and further cement the importance of genetic diversity inclusion in the study of Latin American populations.…”
mentioning
confidence: 99%
“…[7][8][9] Notably, these studies also used self-reported ancestry and found that Europeans and Latin Americans of self-reported European descent had a similar distribution of some risk alleles, suggesting that self-reported ancestry may carry validity in ancestral research. 7,9 In summary, we propose the possibility of ancestry-driven NAFLD and NAFLD-HCC and further cement the importance of genetic diversity inclusion in the study of Latin American populations. However, larger studies including admixture analyses are needed to better understand this interaction.…”
mentioning
confidence: 99%